PENGARUH KUALITAS PELAYANAN INTI DAN KUALITAS PELAYANAN PERIFERAL MELALUI KEPUASAN KONSUMEN PADA MINAT MEREFERENSIKAN (Studi Pada Bus Transjakarta Koridor I) - Firmansyah, Muhammad; Khasanah, Imroatul (Faculty of Economics and Business Diponegoro University, 2016)
The research problem is the number of complaints in Transjakarta passengers on service quality does not go get a solution, although the busway has been operating for 12 years. Proven still found some bus and bus facilities are uncomfortable as well as facilities such as the strip is not sterile and damaged separator, which impact on decreasing the number of Transjakarta bus passengers in 2012 and 2014. This phenomenon is a manifestation of lack of user satisfaction Transjakarta during which felt that quality of services provided Transjakarta management has not been able to meet public expectations.This study aims to 1) examine empirically and analyze the quality of core services to customer satisfaction; 2) empirically examine and analyze the impact of service quality peripherals to customer satisfaction; and 3) examine empirically and analyze the effect of customer satisfaction on interest reference. The population in this study are all service users Transjakarta bus corridor 1 that a minimum of once using Transjakarta bus corridor I 10 times. The sample used as many as 300 people, who divided the morning 100 passengers, 100 passengers during the day and 100 Â passenger afternoon.The results using SPSS shows; 1) the quality of core services direct positive impact on consumer satisfaction Transjakarta users of transport services (Y1). It provides direction that the H1 can be accepted; 2) the quality of core services direct positive effect on the interests of consumers referencing Transjakarta users of transport services. It provides direction that H2 is acceptable; 3) quality of service peripheral direct positive impact on consumer satisfaction Transjakarta users of transport services. It provides direction that the H3 is acceptable; 4) quality of service peripherals (X2) has positive effect directly against the interests of consumers referencing Transjakarta users of transport services. It provides direction that H4 is acceptable; 5) customer satisfaction has positive influence on consumer reference interest Transjakarta users of transport services. It provides direction that H5 is acceptable; 6) the quality of core services referenced positive influence on consumer interest Transjakarta users of transport services through customer satisfaction. It provides direction that H6 is unacceptable, so the variable customer satisfaction serves as an intervening variable; 7) quality of service peripheral positive effect on consumer reference interest Transjakarta users of transport services through customer satisfaction. It provides direction that H7 can be received, so that variable customer satisfaction serves as an intervening variable.